(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Mobile Ad-hoc Networks (MANETs) can be deployed quickly without any existing infrastructure. These networks are useful in many areas, such as emergency assistance, disaster relief, intelligent systems houses, patient monitoring, industrial applications, health monitoring, environmental control, military applications, etc. However ad-hoc networks face many challenges, such as the unpredictable mobility of the network, the limited amount of energy available, security challenges, low computational resources, low memory, etc. There is a need for routing approaches aware of those challenges. Thus, this work aims to provide a secure and context aware ad-hoc network, by changing the frequency of data transmission and routing the packets through reliable links. The proposed approaches has been tested, the results shows an interesting decrease of the transmission throughput coming from malicious nodes, a decrease in the packet loss and an increase of the network lifetime.